Problematic substance use and its associated factors among street youth in Bahir Dar city, Ethiopia - Shegaw, Maregu; Fekadu, Wubalem; Beka, Michael; Menberu, Melake; Yohannes, Kalkidan; Yimer, Solomon; Seid, Mohammed; Necho, Mogesie; Moges, Solomon; Anbesaw, Tamrat (Frontiers in Psychiatry, 2022)
Background: Problematic substance use is becoming a common problem in marginalized groups such as street youths. However, there is a dearth of studies on the prevalence and factors associated with problematic substance use among street youth in Ethiopia. Objective: To determine the prevalence of problematic substance use, and identify it’s associated factors among street youth. Methods: This community based cross-sectional study was conducted between June and July 2020. A total of 252 participants were included in this study. Systematic random sampling was used to recurit participants. Cut down, Annoyed, Guilty feeling, and Eye opening-Adapted to include drugs were used to assess problematic substance use. The data were entered into epidata and exported to SPSS version 25 for analysis. Logistic regression with 95% confidence interval was used to show the strength of association. Statistically significant was set at p value less than 0.5. Results: The prevalence of problematic substance use was 55.8%, 95% CI (49%- 63%). Peer pressures [AOR=3.01, 95% CI: 1.38, 6.59], family conflict [AOR=5.05, 95% CI: 1.67, 15.25], physical abuse [AOR=2.56, 95% CI: 1.11, 5.84] and substance use in the family [AOR=2.85, 95%, CI: 1.29, 6.27] were the factors significantly associated with problematic substance use. Conclusion: The prevalence of problematic substance use was high. It was also found that peer pressure, family conflict, substance use in the family, and physical abuse were the factors associated with problematic substance use. Therefore proper screening and intervention for individuals with problematic substance use are needed and further research should be conducted for marginalized groups.